A cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treatment and a preparation method thereof

CN116983420BActive Publication Date: 2026-10-27HUZHOU ZHANWANG PHARMA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311149984.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2026-10-27
Estimated Expiration
2043-09-07

AI Technical Summary

Technical Problem

[0004]为了解决现有技术中微晶纤维素与无水磷酸氢钙共处理物与药物活性成分(API)直接混合压片后存在混合均匀性差、溶出不达标的问题,本发明提供了一种交联酯化改性微晶纤维素与无水磷酸氢钙共处理物及其制备方法,通过先交联再酯化的双重改性方法改善了微晶纤维素在溶液中的团聚现象并增加了微晶纤维素的比表面积,再以改性后的微晶纤维素与无水磷酸氢钙进行共处理,所制得的共处理物为粉末直压型药物辅料的制备提供了新的解决方案

Benefits of technology

[0027]本发明提供的药物辅料组合物使用交联酯化改性微晶纤维素与无水磷酸氢钙共处理物作为填充剂、优选比表面积大于等于750m2/g的胶态二氧化硅为吸附剂、优选比表面积大于等于3m2/g的硬脂酸镁为润滑剂、优选膨胀体积大于等于28ml的A型羧甲淀粉钠作为崩解剂,从而大幅度提高了与药物活性成分(API)混合后直接压片的均匀性、溶出度和稳定性。该药用辅料组合物适用于稳定性差、遇湿易吸潮、对光和温度敏感的药物活性成分(API)的直接压片,避免了其湿法制粒的复杂工序,有效减少生产所需时间,进一步提升整体工作效率。且相较于传统的湿法制粒,使用粉末直接压片对能源的需求较低,整体制造过程简单,能够节约药品生产的相关成本,实现良好的经济效益目标。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004436518420000041
    Figure BDA0004436518420000041
  • Figure BDA0004436518420000101
    Figure BDA0004436518420000101
  • Figure BDA0004436518420000121
    Figure BDA0004436518420000121
Patent Text Reader

Abstract

The application provides a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-processed product and a preparation method thereof. The double modification method of cross-linking and then esterification improves the agglomeration of microcrystalline cellulose in a solution and increases the specific surface area of the microcrystalline cellulose. Then, the modified microcrystalline cellulose is co-processed with anhydrous calcium hydrogen phosphate. The functional indexes such as the bulk density and the oil absorption value of the co-processed product formed by spray drying are improved to different degrees. The pharmaceutical auxiliary material composition formed by adding colloidal silicon dioxide, type A sodium carboxymethyl starch and magnesium stearate has good mixing uniformity and dissolution effect after being mixed with a pharmaceutical active ingredient (API).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of pharmaceutical and food technology, specifically relating to a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product and its preparation method. Background Technology

[0002] Tablets are the most common type of oral solid dosage form. There are generally two conventional methods for tablet preparation: one is granulation (wet granulation or dry granulation) followed by tableting, and the other is directly compressing the dried and mixed powder into tablets. Tablets produced using the common dry granulation and tableting method suffer from crystal transformation and reduced activity due to high pressure and high temperature, affecting tablet stability; furthermore, the dry granulation and tableting method involves numerous and cumbersome steps. Direct tableting, on the other hand, involves sieving and mixing the active pharmaceutical ingredient (API) powder and suitable excipients, then directly compressing them into tablets without granulation. Compared to the traditional granulation-following tableting method, and the traditional "granulation first, then tableting" process, direct tableting simplifies the tablet manufacturing process, reduces production time, and improves overall efficiency. Simultaneously, this method has lower energy requirements, a simpler manufacturing process, and can reduce costs for pharmaceutical manufacturers, achieving good economic benefits. Furthermore, for some pharmaceutical APIs with poor stability, direct tableting can effectively address limitations and improve drug quality. In summary, direct compression has advantages such as good product stability, high production efficiency, good reproducibility, energy saving, time saving, and cost saving.

[0003] However, direct compression of pharmaceutical excipient powders has certain requirements regarding compressibility and flowability. Chinese invention patent CN115671299A discloses a method for preparing a co-treated product of microcrystalline cellulose and anhydrous dicalcium phosphate. The method involves mixing microcrystalline cellulose and anhydrous dicalcium phosphate, pulping, and spray drying to obtain the co-treated product. The resulting co-treated product exhibits lower bulk density, better flowability, and higher oil and water absorption compared to a direct physical mixture of microcrystalline cellulose and anhydrous dicalcium phosphate. However, direct mixing and compression of this co-treated product with the active pharmaceutical ingredient (API) results in problems such as poor mixing uniformity and inadequate dissolution. Summary of the Invention

[0004] To address the issues of poor mixing uniformity and substandard dissolution when microcrystalline cellulose and anhydrous dicalcium phosphate co-treated products are directly mixed with pharmaceutical active ingredients (APIs) and compressed into tablets in existing technologies, this invention provides a cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product and its preparation method. The dual modification method of first cross-linking and then esterification improves the aggregation phenomenon of microcrystalline cellulose in solution and increases its specific surface area. The modified microcrystalline cellulose is then co-treated with anhydrous dicalcium phosphate. The resulting co-treated product provides a new solution for the preparation of powdered direct-compression pharmaceutical excipients.

[0005] This invention provides a method for preparing a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, characterized by comprising the following steps:

[0006] S1. A crosslinking agent is added to the microcrystalline cellulose suspension to carry out a crosslinking reaction. After the crosslinking reaction is completed, soybean oil is added to carry out an esterification reaction to obtain a crosslinked esterified modified microcrystalline cellulose slurry.

[0007] S2. The cross-linked esterified modified microcrystalline cellulose slurry from step S1 is mixed and stirred with anhydrous dicalcium phosphate wet material, and homogenized to obtain a co-treated emulsion.

[0008] S3. Spray-dry the co-treated emulsion from step S2 to obtain a co-treated product of cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate.

[0009] To improve the dispersibility of microcrystalline cellulose and better suit its application in the preparation of powdered direct-compression pharmaceutical excipients, as well as to further enhance the mixing uniformity and dissolution effect of pharmaceutical excipients, this invention performs a dual modification on microcrystalline cellulose: first crosslinking, then esterification. In this invention, dialdehyde compounds are used as crosslinking agents, generally including glutaraldehyde and glyoxal. Dialdehyde compounds have two symmetrical aldehyde groups (-CHO), which can first react with the hydroxyl groups (-OH) in microcrystalline cellulose to form hemiacetals, and then crosslink to form stable acetal compounds. The crosslinking reaction leads to the formation of crosslinking bridges between microcrystalline cellulose molecules, increasing the number of crosslinking points between microcrystalline cellulose molecules. Based on the crosslinking modification, this invention esterifies the uncrosslinked hydroxyl groups (-OH) on microcrystalline cellulose with fatty acids from soybean oil. Soybean oil, as a commonly used vegetable oil, is not only readily available and has good biocompatibility and biodegradability, but also contains a variety of fatty acids, including saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids, especially rich in polyunsaturated fatty acids such as linoleic acid and linolenic acid. The introduction of fatty acid groups from soybean oil further increases the molecular weight and fiber strength of cross-linked modified microcrystalline cellulose. The microcrystalline cellulose obtained through pre-cross-linking followed by esterification modification possesses nanoscale size and high crystallinity, along with a larger specific surface area. It can be uniformly and stably dispersed in solution, and its mechanical strength is significantly improved. This cross-linked esterified modified microcrystalline cellulose is of great significance for the preparation of powdered direct-compression pharmaceutical excipients, as it can further improve the mixing uniformity and dissolution effect of powdered direct-compression pharmaceutical excipients while maintaining high fluidity, high oil absorption, and high water absorption.

[0010] Specifically, in step S1, the concentration of microcrystalline cellulose in the microcrystalline cellulose suspension is 20-30 wt.%, more preferably 25 wt.%; the microcrystalline cellulose can be commercially available or prepared in-house. Commercially available conventional microcrystalline cellulose, such as nano-microcrystalline cellulose, or its co-processed products, are all suitable for this invention. Microcrystalline cellulose can also be prepared by the following method: mixing wood pulp with dilute sulfuric acid, heating and acidifying, cooling, adding ammonia water for neutralization, and then filtering, washing, drying, and sieving the neutralized solution to obtain microcrystalline cellulose. The preferred method for preparing the microcrystalline cellulose is as follows: wood pulp is mixed with 5-20 wt.% dilute sulfuric acid at a weight ratio of 1:(10-20), heated to 70-120°C for acid hydrolysis for 0.5-2 hours, cooled to 50-70°C, and then neutralized to pH 5-7 by adding 10-30 wt.% ammonia water; the neutralized solution is pumped into a plate and frame filter press for filtration, and washed with reverse osmosis water until the conductivity of the washing solution is less than 200 μS / cm. -1 The filter cake is obtained by pressing and drying. It is then fed into a flash dryer for further drying. The parameters of the flash dryer are set as follows: inlet air temperature 130–160℃, outlet air temperature 60–90℃. The dried filter cake is then sieved through an 80–100 mesh vibrating sieve to obtain microcrystalline cellulose.

[0011] Preferably, in step S1, before adding the crosslinking agent, the microcrystalline cellulose suspension is first subjected to micronization treatment, which includes ball milling, high-pressure homogenization, emulsification, etc., and ball milling treatment is even more preferred.

[0012] Preferably, in step S1, the crosslinking agent is selected from one or a mixture of two of glutaraldehyde and glyoxal. In typical dialdehyde crosslinking agents, the number of methylene groups between the two carbonyl pairs has a certain influence on the binding effect of the crosslinking points, thus affecting the crystallinity and fiber strength of microcrystalline cellulose. Furthermore, the crosslinking modification of microcrystalline cellulose can also be controlled by adjusting parameters such as the concentration of the crosslinking agent and reaction conditions to control the degree of crosslinking and the formation of the crosslinked structure.

[0013] Preferably, in step S1, the amount of crosslinking agent added is 0.1 to 2 wt.% of the microcrystalline cellulose, more preferably 0.3 to 1.5 wt.%.

[0014] Preferably, in step S1, the temperature of the crosslinking reaction is 40–60°C and the time is 2–4 hours.

[0015] Preferably, in step S1, the amount of soybean oil added is 20-50 wt.% of the microcrystalline cellulose.

[0016] Preferably, in step S1, the esterification reaction is carried out at a temperature of 100–150°C for 3–4 hours.

[0017] Preferably, in step S1, the esterification reaction is carried out using ethanol as a solvent, and the mass ratio of soybean oil to ethanol is 1:(0.8-1.2), more preferably 1:1.

[0018] Specifically, in step S2, the anhydrous dicalcium phosphate wet material can be prepared by the following method: a 15-30 wt.% phosphoric acid solution is prepared and added to a reaction vessel, then heated to 40-50°C; a 15-25 wt.% calcium carbonate slurry is prepared and added to the reaction vessel at a rate of 1.5-3.5 L / min, while simultaneously heating the solution in the reaction vessel to 60-70°C and continuously stirring at a rate of 150-250 rpm to allow the calcium carbonate slurry to react with the phosphoric acid solution. After the calcium carbonate slurry is added... Continue stirring until the pH of the solution reaches 5.0–5.5, and the temperature drops to 50–60℃. Stir and maintain the temperature for 0.5–1.5 h to obtain slurry one. Prepare 10–15 wt.% lime milk and add it to the above slurry one at a rate of 1.0–2.5 L / min. While adding the lime milk, stir at a rate of 130–200 rpm. After the lime milk is added, continue stirring for 15–20 min until the pH of the solution reaches 6–7. Stir and maintain the temperature for 1–1.5 h, and centrifuge to obtain anhydrous dicalcium phosphate wet material.

[0019] Preferably, in step S2, the emulsion particle size of the co-treated emulsion does not exceed 10 μm, and more preferably is 1 to 8 μm.

[0020] Preferably, in step S3, the weight ratio of cross-linked esterified modified microcrystalline cellulose to anhydrous dicalcium phosphate in the co-treated product is 1:(0.95–2.05). By adjusting the ratio, different specifications of products with similar bulk density, particle size distribution, and physicochemical properties to active pharmaceutical ingredients (APIs) can be customized.

[0021] Preferably, in step S3, the spray drying process is completed using a centrifugal spray dryer; the parameters of the spray dryer are set as follows: inlet air temperature 135~280℃, outlet air temperature 70~140℃, atomizer speed 8~30Hz, and feed flow rate 0.3~0.6m³ / h. 3 / h, negative pressure 500~1300Pa.

[0022] Preferably, in step S3, the material after spray drying is subjected to iron removal treatment, which is completed by an iron remover; the parameters of the iron remover are set to 80,000 to 120,000 Gauss.

[0023] This invention also provides a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium phosphate co-treated product, prepared by the above method. The bulk density of the cross-linked esterified modified microcrystalline cellulose and anhydrous calcium phosphate co-treated product ranges from 0.2 to 0.8 g / cm³. 3 The particle size D50 ranges from 40 to 140 μm, and the drying loss is no more than 7%. In conventional co-treatment of microcrystalline cellulose and anhydrous dicalcium phosphate, due to the poor stability of microcrystalline cellulose, the pharmaceutical preparations made by mixing it with the active pharmaceutical ingredient (API) after co-treatment with anhydrous dicalcium phosphate do not meet the requirements for mixing uniformity, dissolution effect, oil absorption value, and other indicators. However, the co-treatment formed by mixing, emulsifying, and spray drying cross-linked esterified microcrystalline cellulose and anhydrous dicalcium phosphate shows that the bulk density, oil absorption value, and other functional indicators are improved to varying degrees. The pharmaceutical excipient composition formed by adding adsorbent (colloidal silica), disintegrant (sodium carboxymethyl starch type A), and lubricant (magnesium stearate) and mixing it with the active pharmaceutical ingredient (API) exhibits good mixing uniformity and dissolution effect.

[0024] The present invention also provides a pharmaceutical excipient composition comprising a cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product.

[0025] Preferably, the pharmaceutical excipient composition comprises, by weight, the following components:

[0026]

[0027] The pharmaceutical excipient composition provided by this invention uses cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated material as a filler, preferably with a specific surface area greater than or equal to 750 m². 2 / g of colloidal silica is used as the adsorbent, preferably with a specific surface area greater than or equal to 3m². 2 Magnesium stearate ( / g) is used as a lubricant, and sodium carboxymethyl starch (Type A) with an expansion volume of ≥28ml is preferred as a disintegrant, thereby significantly improving the uniformity, dissolution, and stability of direct tableting after mixing with the active pharmaceutical ingredient (API). This pharmaceutical excipient composition is suitable for the direct tableting of APIs with poor stability, hygroscopicity, and sensitivity to light and temperature, avoiding the complex wet granulation process, effectively reducing production time, and further improving overall work efficiency. Furthermore, compared to traditional wet granulation, direct tableting using powder requires less energy, has a simpler overall manufacturing process, and can save on relevant drug production costs, achieving good economic benefits.

[0028] The beneficial effects of this invention are as follows: Compared to the co-treated microcrystalline cellulose and anhydrous dicalcium phosphate in the prior art, this invention proposes a dual modification of microcrystalline cellulose, involving first cross-linking and then esterification. This results in microcrystalline cellulose possessing both nanoscale size and higher crystallinity and a larger specific surface area. Furthermore, co-treating it with anhydrous dicalcium phosphate solves the problem of uneven mixing caused by the higher bulk density of anhydrous dicalcium phosphate and the lower bulk density of microcrystalline cellulose, which affects product dissolution and reduces efficacy. The resulting co-treated compound not only possesses low bulk density, high flowability, and high oil and water absorption, but also significantly improves the mixing uniformity and dissolution effect after direct mixing and tableting with the active pharmaceutical ingredient (API). Simultaneously, the cross-linking-then-esterification modification method provided by this invention also offers new insights into improving the performance of microcrystalline cellulose. Detailed Implementation

[0029] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. Unless otherwise specified, the methods used in the embodiments of the present invention are conventional methods, and the reagents used are commercially available.

[0030] Example 1:

[0031] This embodiment provides a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, the preparation method of which is as follows:

[0032] S1. Preparation of cross-linked esterified modified microcrystalline cellulose: 200 kg of wood pulp and 10 wt.% dilute sulfuric acid were mixed in a reactor at a mass ratio of 1:15. The mixture was acid-hydrolyzed at 95–100 °C for 1.5 hours to obtain an acid hydrolysate. The hydrolysate was cooled to 65 °C, and 15 wt.% ammonia was added to adjust the pH to 6.5. The neutralized solution was pumped into a plate and frame filter press for filtration. Then, primary reverse osmosis water was added for washing until the conductivity of the washing solution was less than 200 μS / cm. -1 The microcrystalline cellulose filter cake was obtained by pressing and drying. The filter cake was then fed into a flash dryer and dried at an inlet air temperature of 150°C and an outlet air temperature of 80°C. The dried material was collected and passed through a 100-mesh ultrasonic sieve to obtain microcrystalline cellulose. The microcrystalline cellulose obtained above was prepared into a 25 wt% suspension with pure water and micronized using a ball mill at 500 r / min for 60 minutes. The solution was transferred to a crosslinking reactor, and 0.3 wt.% glutaraldehyde (by weight of microcrystalline cellulose) was added. The mixture was stirred at 55°C for 3 hours to obtain crosslinked modified microcrystalline cellulose. A soybean oil-ethanol mixture was added to the reactor containing the crosslinked modified microcrystalline cellulose, wherein soybean oil and ethanol comprised 20 wt.% of the weight of microcrystalline cellulose. After stirring evenly, the mixture was reacted at 110–115°C for 4 hours to obtain a crosslinked esterified modified microcrystalline cellulose slurry.

[0033] S2. Preparation of co-treated emulsion: A 15 wt.% phosphoric acid solution was added to the reactor and then heated to 40°C. A 25 wt.% calcium carbonate slurry was added to the reactor at a rate of 1.5 L / min, while the solution in the reactor was heated to 65°C and continuously stirred at a rate of 200 rpm to allow the calcium carbonate slurry to react with the phosphoric acid solution. After the calcium carbonate slurry was added, stirring continued until the pH of the solution reached 5, the temperature was lowered to 60°C, and stirring was maintained for 1.5 h to obtain slurry one. A 15 wt.% lime slurry was added to slurry one at a rate of 2.5 L / min, while stirring at a rate of 150 rpm. After the lime slurry was added, stirring continued for 20 min until the pH of the solution reached 6, and stirring was maintained for 1.5 h. The solution was then centrifuged to obtain anhydrous dicalcium phosphate wet material. The cross-linked esterified modified microcrystalline cellulose slurry from step S1 was mixed with anhydrous dicalcium phosphate wet material at a dry weight ratio of 1:1. Water was added to prepare a slurry with a solid content of 30%. The stirring speed was controlled at 300 rpm, and the mixture was stirred for 10 min and then ball-milled for 2 h to obtain a co-treated emulsion with an emulsion particle size of 10 μm.

[0034] S3. Spray Drying: Pump the reaction solution into the spray dryer at an inlet air temperature of 280℃, an outlet air temperature of 140℃, an atomizer speed of 12Hz, and a feed flow rate of 0.5m³ / h. 3 Spray drying was carried out at a negative pressure of 1060 Pa / h. The spray-dried material was collected and subjected to iron removal by an iron remover at 80000 Gauss. After iron removal, it was passed through a 100-mesh ultrasonic sieve, and the cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product was obtained, which is sample one.

[0035] Example 2:

[0036] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. Its preparation method is basically the same as that of Example 1, except that the amount of glutaraldehyde added in step S1 accounts for 0.05 wt.% of the weight of microcrystalline cellulose, and sample two is obtained.

[0037] Example 3:

[0038] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, the preparation method of which is basically the same as that of Example 1, except that the amount of glutaraldehyde added in step S1 accounts for 1 wt.% of the weight of microcrystalline cellulose, and sample three is obtained.

[0039] Example 4:

[0040] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. Its preparation method is basically the same as that of Example 1, except that the amount of glutaraldehyde added in step S1 accounts for 2 wt.% of the weight of microcrystalline cellulose, and sample four is obtained.

[0041] Example 5:

[0042] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, the preparation method of which is basically the same as that of Example 1, except that glyoxal is used as a cross-linking agent instead of glutaraldehyde in step S1, and sample five is obtained.

[0043] Example 6:

[0044] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, the preparation method of which is basically the same as that of Example 5, except that the amount of glyoxal added in step S1 accounts for 2 wt.% of the weight of microcrystalline cellulose, and sample six is ​​obtained.

[0045] Example 7:

[0046] This embodiment provides a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, the preparation method of which is as follows:

[0047] S1. Preparation of cross-linked esterified modified microcrystalline cellulose: 200 kg of wood pulp and 10 wt.% dilute sulfuric acid were mixed in a reactor at a mass ratio of 1:15. The mixture was acid-hydrolyzed at 95–100 °C for 1.5 hours to obtain an acid hydrolysate. The hydrolysate was cooled to 65 °C, and 15 wt.% ammonia was added to adjust the pH to 6.5. The neutralized solution was pumped into a plate and frame filter press for filtration. Then, primary reverse osmosis water was added for washing until the conductivity of the washing solution was less than 200 μS / cm. -1 The microcrystalline cellulose filter cake was obtained by pressing and drying. The filter cake was then fed into a flash dryer and dried at an inlet air temperature of 150°C and an outlet air temperature of 80°C. The dried material was collected and passed through a 100-mesh ultrasonic sieve to obtain microcrystalline cellulose. The microcrystalline cellulose obtained above was prepared into a 30 wt% suspension with pure water and micronized using a ball mill at 500 r / min for 60 minutes. The solution was transferred to a crosslinking reactor, and 0.5 wt.% glutaraldehyde (by weight of microcrystalline cellulose) was added. The mixture was stirred at 45°C for 4 hours to obtain crosslinked modified microcrystalline cellulose. A soybean oil-ethanol mixture was added to the reactor containing the crosslinked modified microcrystalline cellulose. The soybean oil-ethanol mixture comprised 30 wt.% of the microcrystalline cellulose by weight, and the ethanol comprised 24 wt.% of the microcrystalline cellulose by weight. After stirring evenly, the mixture was reacted at 135–140°C for 3 hours to obtain a crosslinked esterified modified microcrystalline cellulose slurry.

[0048] S2. Preparation of co-treated emulsion: A 15 wt.% phosphoric acid solution was added to the reactor and then heated to 40°C. A 25 wt.% calcium carbonate slurry was added to the reactor at a rate of 1.5 L / min, while the solution in the reactor was heated to 65°C and continuously stirred at a rate of 200 rpm to allow the calcium carbonate slurry to react with the phosphoric acid solution. After the calcium carbonate slurry was added, stirring continued until the pH of the solution reached 5, the temperature was lowered to 60°C, and stirring was maintained for 1.5 h to obtain slurry one. A 15 wt.% lime slurry was added to slurry one at a rate of 2.5 L / min, while stirring at a rate of 150 rpm. After the lime slurry was added, stirring continued for 20 min until the pH of the solution reached 6, and stirring was maintained for 1.5 h. The solution was then centrifuged to obtain anhydrous dicalcium phosphate wet material. The cross-linked esterified modified microcrystalline cellulose slurry from step S1 was mixed with anhydrous dicalcium phosphate wet material at a dry weight ratio of 1:2. Water was added to prepare a slurry with a solid content of 30%. The stirring speed was controlled at 350 rpm, and the mixture was stirred for 10 min before ball milling to obtain a co-treated emulsion with an emulsion particle size of 10 μm.

[0049] S3. Spray Drying: Pump the reaction solution into the spray dryer at an inlet air temperature of 200℃, an outlet air temperature of 100℃, an atomizer speed of 15Hz, and a feed flow rate of 0.5m³ / h. 3Spray drying was carried out at a negative pressure of 1060 Pa / h. The spray-dried material was collected and subjected to iron removal by an iron remover at 80000 Gauss. After iron removal, it was passed through a 100-mesh ultrasonic sieve, and the cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product was obtained, which is sample seven.

[0050] Example 8:

[0051] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. The preparation method is basically the same as that in Example 7, except that the soybean oil and ethanol mixture added accounts for 10 wt.% of the weight of microcrystalline cellulose and 8 wt.% of the weight of microcrystalline cellulose, thus obtaining sample eight.

[0052] Example 9:

[0053] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. The preparation method is basically the same as that in Example 7, except that the soybean oil and ethanol mixture added accounts for 50 wt.% of the weight of microcrystalline cellulose and 60 wt.% of the weight of microcrystalline cellulose, thus obtaining sample nine.

[0054] Example 10:

[0055] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. The preparation method is basically the same as that in Example 1, except that in step S2, after ball milling for 3 hours, a co-treated product emulsion is obtained with a particle size of 8 μm, and sample 10 is obtained.

[0056] Example 11:

[0057] This embodiment provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. The preparation method is basically the same as that in Example 7, except that in step S2, after homogenization with a high-pressure homogenizer for 2 hours, a co-treated product emulsion is obtained. The emulsion particle size is 5 μm, and sample eleven is obtained.

[0058] Comparative Example 1:

[0059] This comparative example provides a co-treated product of microcrystalline cellulose and anhydrous calcium hydrogen phosphate, which is prepared as follows: the microcrystalline cellulose obtained in Example 1 is directly taken and prepared according to the methods of steps S2 and S3 to obtain the co-treated product of microcrystalline cellulose and anhydrous calcium phosphate, which is sample twelve.

[0060] Comparative Example 2:

[0061] This comparative example provides a cross-linked modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, which is prepared as follows: take the cross-linked modified microcrystalline cellulose obtained in Example 1, and prepare it according to the methods of steps S2 and S3 to obtain the cross-linked modified microcrystalline cellulose and anhydrous calcium phosphate co-treated product, which is sample thirteen.

[0062] Comparative Example 3:

[0063] This comparative example provides a co-treated product of esterified modified microcrystalline cellulose and anhydrous calcium phosphate, which is prepared as follows: The microcrystalline cellulose obtained in Example 1 is added to a reaction vessel along with a soybean oil-ethanol mixture, wherein the soybean oil accounts for 20 wt.% of the weight of the microcrystalline cellulose and the ethanol accounts for 20 wt.% of the weight of the microcrystalline cellulose. After stirring evenly, the mixture is reacted at a temperature range of 110-115℃ for 4 hours to obtain esterified modified microcrystalline cellulose. The product is then prepared according to steps S2 and S3 to obtain the co-treated product of esterified modified microcrystalline cellulose and anhydrous calcium phosphate, which is sample fourteen.

[0064] Comparative Example 4:

[0065] This comparative example provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. The preparation method is basically the same as that of Example 1, except that the co-treated product emulsion is obtained after ball milling for 1.5 h in step S2. The emulsion particle size is 12 μm, and sample 15 is obtained.

[0066] Comparative Example 5:

[0067] This comparative example provides another cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product. The preparation method is basically the same as that of Example 7, except that the co-treated product emulsion is obtained after ball milling for 1 hour in step S2. The emulsion particle size is 15 μm, and sample sixteen is obtained.

[0068] The physicochemical properties of the samples prepared in Examples 1-11 and Comparative Examples 1-5 were analyzed, and the results are shown in Table 1. Among them:

[0069] "Loose density" refers to the ratio of the mass m of the tablet powder to its filling volume V (including the voids between the powder particles) when the tablet is not vibrated, and is expressed in g / ml.

[0070] “Particle size D50” refers to the particle size at which the cumulative particle size distribution percentage of a sample reaches 50%.

[0071] The method for testing oil absorption is as follows:

[0072] a. Place the sample on a flat plate and add refined linseed oil dropwise using a burette. Each time, the amount of oil added should not exceed 10 drops. After adding the oil, press and grind it with a spatula to allow the oil to penetrate into the test sample.

[0073] b. Continue adding oil at this rate until the oil and sample form a clump. From this point on, after each drop, grind thoroughly with a spatula. The endpoint is reached when a uniform paste of consistent consistency is formed, which is neither cracked nor broken, and can adhere to the plate.

[0074] c. Record the amount of oil consumed, in ml / 100g. The entire operation should be completed within 20-25 minutes.

[0075] The test method for water absorption is the same as the test method for oil absorption.

[0076] The "angle of repose" is the smallest angle between an inclined plane and a horizontal surface when an object placed on the inclined plane is in a critical state of sliding down the inclined plane. It is related to density, surface area and shape of particles, and the coefficient of friction of the material.

[0077] Table 1. Physicochemical Index Analysis

[0078]

[0079] Combined with Table 1 and Examples 1 and 1, it can be seen that the cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-spray dried exhibit significantly lower bulk density and higher oil absorption than the unmodified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product. This further verifies the degree to which cross-linking esterification modification improves the performance of the co-treated microcrystalline cellulose and anhydrous dicalcium phosphate. Sample 4 showed better oil and water absorption capacity (138 ml / 100g and 145 ml / 100g respectively) and better bulkiness, indicating that as the amount of cross-linking agent increased to 2 wt.% of the microcrystalline cellulose weight, cross-linking modification further improved the specific surface area of ​​the co-treated product. The choice of cross-linking agent during the cross-linking modification process has a certain influence on the crystallinity and mechanical properties of microcrystalline cellulose. Currently, glutaraldehyde is the most widely used dialdehyde crosslinking agent. However, compared to glyoxal, glutaraldehyde still has three methylene groups between its two carbonyl pairs, which have a certain binding effect on the crosslinking points after crosslinking. This results in the crystallinity of microcrystalline cellulose crosslinked with glutaraldehyde being slightly lower than that crosslinked with glyoxal, thus affecting the bulk density of the co-treated product. Referring to Table 1 and Examples 7-9 and Comparative Example 2, it can be seen that when the amount of soybean oil added is 20-50 wt.% of the microcrystalline cellulose, further esterification modification of the microcrystalline cellulose on the basis of crosslinking modification further improves the oil absorption effect of the co-treated product. As can be seen from Table 1 and Examples 10-11 and Comparative Examples 4-5, the emulsion particle size of the co-treated emulsion after homogenization in step S2 also has a certain influence on the performance of the final product. When the emulsion particle size does not exceed 10 μm, the obtained cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product has a lower bulk density, which is beneficial to improving the dissolution rate and content uniformity of the drug when used as a pharmaceutical excipient.

[0080] Example 12:

[0081] In this embodiment, pharmaceutical excipient compositions were prepared using the samples provided in Example 1 and Comparative Example 1, respectively. The specific preparation methods are as follows: 18.6 kg of the prepared sample, 0.1 kg of colloidal silica, 0.2 kg of magnesium stearate, and 0.1 kg of sodium carboxymethyl starch (Type A) were mixed evenly to obtain pharmaceutical excipient compositions A and B. The specific surface area of ​​the colloidal silica was 775 m². 2 / g; The specific surface area of ​​magnesium stearate is 3.5m². 2 / g; Sodium carboxymethyl starch type A, according to the Chinese Pharmacopoeia 2020 edition, Part IV, showed an expansion volume of 31ml.

[0082] Amlodipine besylate, which has poor stability, readily absorbs moisture, and is extremely sensitive to light and temperature, was used as the active pharmaceutical ingredient (API). It was mixed with either pharmaceutical excipient composition A or B, and tablets were prepared by direct compression to study the performance of the pharmaceutical excipient compositions. As a comparison, this embodiment also provides a method for preparing amlodipine besylate tablets using wet granulation, as detailed below:

[0083] Preparation of amlodipine besylate tablets by direct compression method:

[0084] 1 kg of amlodipine besylate raw material was passed through a 100-mesh sieve, and 19 kg of the pharmaceutical excipient composition A or B prepared in Example 12 was passed through a 60-mesh sieve. The mixture was then directly compressed into tablets, with the hardness controlled at 80-100 N, to obtain the corresponding amlodipine besylate tablets, tablet one and tablet two. The purity of amlodipine besylate in tablets one and two was 99.9%, and the total impurities were 0.06%.

[0085] Preparation of amlodipine besylate tablets by wet granulation:

[0086] (1) Weigh each component according to the following formula, and pass amlodipine besylate through a 100-mesh sieve. Take the raw material passing through the sieve and set it aside:

[0087] Amlodipine besylate 1 kg; pH 103 type microcrystalline cellulose 17.4 kg; anhydrous dicalcium phosphate 8.6 kg; internally added sodium carboxymethyl starch 0.43 kg; externally added type A sodium carboxymethyl starch 0.72 kg; KG802 type microcrystalline cellulose 1.44 kg; premixed magnesium stearate 0.14 kg; total mixed magnesium stearate 0.14 kg; wherein:

[0088] The density of anhydrous calcium phosphate is 0.82 g / cm³. 3 Its particle size D50 range is 119 μm, and its drying loss is 0.4%.

[0089] The bulk density of PH103 type microcrystalline cellulose is 0.29 g / cm³. 3 Its particle size D50 range is 103 μm, and its drying loss is 0.6%;

[0090] The bulk density of KG802 type microcrystalline cellulose is 0.21 g / cm³. 3 Its particle size D50 ranges from 95 μm, and its drying loss is 2.8%.

[0091] The specific surface area of ​​magnesium stearate is 3.5 m². 2 / g;

[0092] Sodium carboxymethyl starch type A, when tested according to the Chinese Pharmacopoeia 2020 edition, Part IV, showed an expansion volume of 16 ml.

[0093] (2) The formula amount of microcrystalline cellulose PH103, anhydrous dicalcium phosphate and sodium carboxymethyl starch were placed in a wet granulator and mixed evenly. Then 10.4 kg of purified water was added to make a soft material. The material was passed through a 30-mesh nylon sieve and granulated by shaking. The resulting granules were placed in an oven at 55°C and dried for 4 hours to make the moisture content <2.5%. The granules were then passed through a 20-mesh sieve to obtain the first granules.

[0094] (3) Amlodipine benzylsulfonic acid after passing through a 100-mesh sieve, along with the formulated amount of microcrystalline cellulose KG802, sodium carboxymethyl starch, premixed magnesium stearate, and the first particle mentioned above, are placed in a three-dimensional mixer and mixed at a frequency of 25 Hz for 20 min to obtain the second particle.

[0095] (4) Add the total amount of magnesium stearate in the formulation to the three-dimensional mixer and mix it with the second particle at a frequency of 25 Hz for 10 min. Place the resulting formulation particles in a rotary tablet press for tableting and control the hardness to 80-100 N to obtain tablets. The purity of the tablets is 99.9% and the total impurities are 0.06%.

[0096] The prepared tablets 1, 2, and 3 underwent various performance tests, as detailed below:

[0097] 1. Tests on the content, dissolution rate, and content uniformity of related substances.

[0098] The contents of related substances, dissolution rate, and content uniformity of tablets 1, 2, and 3 were compared, and the results are shown in Table 2. Among them:

[0099] The content of related substances was determined according to the method for determination of related substances in amlodipine besylate tablets, Part II of the 2020 edition of the Chinese Pharmacopoeia;

[0100] The content uniformity was determined according to the method for determining the content uniformity of amlodipine besylate tablets in the 2020 edition of the Chinese Pharmacopoeia, Part II.

[0101] Dissolution was determined according to the method for dissolution determination of amlodipine besylate tablets in the 2020 edition of the Chinese Pharmacopoeia, Part II.

[0102] Table 2. Content, dissolution rate, and content uniformity of related substances in different tablets

[0103]

[0104] Table 2 shows that the related substance content, dissolution rate, and content uniformity of tablets 1 and 3 are comparable. This indicates that the effect of using the pharmaceutical excipient composition provided by this invention to prepare amlodipine besylate tablets by direct powder compression is the same as that of the traditional wet granulation method. Compared with tablet 2, tablet 1 shows significantly higher related substance content and content uniformity, as well as a substantial increase in dissolution rate. This indicates that the high specific surface area cross-linked esterified modified microcrystalline cellulose significantly improves the related substance content, dissolution rate, and content uniformity of amlodipine besylate tablets. The pharmaceutical excipient composition provided by this invention, with cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product as the main components, can not only prepare amlodipine besylate tablets by direct compression, but also significantly improve the dissolution rate and content uniformity of the product, while effectively reducing the related substance content in the product.

[0105] 2. High temperature test

[0106] The prepared tablets 1, 2, and 3 were placed in a constant temperature chamber at 60°C for 10 days. Samples were taken before (0d) and after the 10th day (10d) to observe the changes in the content of related substances. The test results are shown in Table 3.

[0107] Table 3. Related substance content of each tablet in high temperature test

[0108]

[0109] 3. High humidity test

[0110] The prepared tablets 1, 2, and 3 were placed in a constant temperature sealed container with a relative humidity of 90% for 10 days. Samples were taken before placement (0d), on the 5th day (5d), and on the 10th day (10d) to observe the changes in the content of related substances. The test results are shown in Table 4.

[0111] Table 4. Related substance content of each tablet in the high humidity test

[0112]

[0113] 4. Strong light irradiation test

[0114] Tablets 1, 2, and 3 were placed under light intensity of 4500 Lx for 10 days. Samples were taken before (0d), on the 5th (5d), and on the 10th (10d) day after placement to observe the changes in the content of related substances. The test results are shown in Table 5.

[0115] Table 5. Related substance content of each tablet in the high-intensity light test

[0116]

[0117] 5. Accelerated Testing

[0118] Tablets 1, 2, and 3 were placed at a temperature of 40±2℃ and a relative humidity of 75±5% for 6 months. Samples were taken in the sixth month to observe the changes in the content of related substances. The test results are shown in Table 6.

[0119] Table 6. Related substance content of each tablet in accelerated testing

[0120]

[0121] High temperature, high humidity, strong light irradiation, and accelerated testing demonstrated that the content of related substances in tablets 1 and 3 increased considerably under various influencing factors. This indicates that the effect of preparing amlodipine besylate tablets using the pharmaceutical excipient composition provided by this invention via direct powder compression is the same as that of the traditional wet granulation method. Combining tablets 1 and 2, tablet 2 showed a greater increase in the content of related substances under various influencing factors, reflecting the enhanced stability of amlodipine besylate by the high specific surface area cross-linked esterified modified microcrystalline cellulose.

[0122] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope of the present invention.

Claims

1. A method for preparing a cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product, characterized in that, Includes the following steps: S1. A crosslinking agent is added to a microcrystalline cellulose suspension to carry out a crosslinking reaction. After the crosslinking reaction is completed, soybean oil is added to carry out an esterification reaction to obtain a crosslinked esterified modified microcrystalline cellulose slurry. The crosslinking agent is selected from one or a mixture of two of glutaraldehyde and glyoxal. The amount of crosslinking agent added is 0.1~2 wt.% of the microcrystalline cellulose by weight; the amount of soybean oil added is 20~50 wt.% of the microcrystalline cellulose by weight. S2. The cross-linked esterified modified microcrystalline cellulose slurry from step S1 is mixed and stirred with anhydrous dicalcium phosphate wet material, and homogenized to obtain a co-treated emulsion; the emulsion particle size of the co-treated emulsion does not exceed 10 μm. S3. Spray-dry the co-treated emulsion from step S2 to obtain a cross-linked esterified modified microcrystalline cellulose anhydrous calcium hydrogen phosphate co-treated product.

2. The preparation method according to claim 1, characterized in that, In step S1, the esterification reaction is carried out at a temperature of 100-150°C for 3-4 hours.

3. The preparation method according to claim 1, characterized in that, In step S3, the spray drying process is completed using a centrifugal spray dryer; the parameters of the spray dryer are set as follows: inlet air temperature 135~280℃, outlet air temperature 70~140℃, atomizer speed 8~30Hz, and feed flow rate 0.3~0.6m³ / h. 3 / h, negative pressure 500~1300 Pa.

4. The preparation method according to claim 1, characterized in that, In step S3, the weight ratio of cross-linked esterified modified microcrystalline cellulose to anhydrous dicalcium phosphate in the prepared cross-linked esterified modified microcrystalline cellulose co-treated product is 1:(0.95~2.05).

5. The cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product prepared by any one of claims 1 to 4, characterized in that, The bulk density of the cross-linked esterified modified microcrystalline cellulose and anhydrous dicalcium phosphate co-treated product ranges from 0.2 to 0.8 g / cm³. 3 The particle size D50 ranges from 40 to 140 μm, and the drying loss is no more than 7%.

6. A pharmaceutical excipient composition, characterized in that, This includes the cross-linked esterified modified microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treated product as described in claim 5.

Citation Information

Patent Citations

  • Esterification modification method of microcrystalline cellulose

    CN102702361A

  • Easily-water dispersible nanocrystalline cellulose and preparation method thereof

    CN103588886A

  • Preparation method of microcrystalline cellulose and anhydrous calcium hydrogen phosphate co-treatment substance

    CN115671299A